Ontology of folktales in the Greater Mekong Subregion. (2018) - Tuamsuk, Kulthida; Chansanam, Wirapong; Kaewboonma, Nattapong
The goal of this research is to use the digital humanities research concept in the folktales study in the Greater Mekong Subregion (GMS). This paper presents the second phase of the research, focusing on developing ontologies of folktales in the GMS. The ontology development comprised two processes: (1) ontology design and development and (2) ontology documentation. In both processes, domain knowledge and ontology of folktales were collected, captured, revised, and evaluated by experts in the field of folktale studies, literary studies, Asian studies, and ontology development. The outcome of this research is domain ontologies for folktales in the GMS. Approximately, 74 concepts of folktales in the GMS have been defined and classified into classes and subclasses, including some necessary scope notes and relationships of the topics. This developed ontology will be useful for the development of a semantic digital library of GMS folktales in the next steps of this research.